(untitled) (Journal of Hama University, 2024)
Intertextuality or the overlapping of texts is a technical technique that has proven its effectiveness in the literary text and is based on the poet’s invocation of different texts in the memorial inventory with the aim of enriching his new text. Reading and interpretation, as it was launched as a reading strategy through which the text is read in the light of the texts overlapping and intersecting with them, and then moved to the field of interpretation; Highlighting the role of the recipient as an active reader participating in the creative process and even as a second producer of the text; Intertextuality can only be revealed if the recipient is aware of the textual overlaps between the texts, and it is not possible to determine the influence of a later text on the previous text if the recipient is ignorant of these texts in the first place. His participation and the creator in the experiences, the cultural heritage and the sources on which the intertextual text is based and stored in the collective memory of both of them. The process of reading, interpreting and enjoying the awareness of textual structures begins when the text is the crossroads of these units whose production is shared by the creator (the sender) and the text (the reader (the message) Although the term intertextuality is one of the relatively recent terms in literary studies and criticism, it has roots in our Arab rhetorical and critical heritage. Citation, and others.